Perfil metabólico e hormonal de novilhos F1 Holandês x Gir submetidos à respirometria, sob diferentes planos nutricionais, em jejum e realimentação - Paolo Antonio Dutra Vivenza (2012)
The objective of this work was to study the metabolic and hormonal profile of steers during evaluate of nutritional requirements by the respirometric technique. Three separate analyzes were performed: assessment of nutritional plans against metabolic and hormonal profile; evaluation of metabolic and hormonal profile in steers undergoing fasting period of 72 hours and during post-fasting feedback. Were used 15 steers F1 (Gir x Holstein) with an average initial weight of 304 kg. These animals were randomized allocated into three groups and fed diets to provide mild gains (group called maintenance), intermediate gains (group called average gain) and free weight gains (group called free gain). The variables analyzed were cortisol, insulin, glucose, beta-hydroxybutyrate (-BHB), non-esterified fatty acids (NEFA), urea, creatinine, total protein, albumin, globulin, triglycerides, cholesterol, gamma glutamyl transferase (GGT), aspartate aminotransferase (AST) and hematocrit. Evaluating the nutritional plan against metabolic and hormonal profile, it is observed that different taxes eating plans promoted differences in blood glucose and insulin, and the animals of group maintenance have the lowest values of these components. While receiving diet that met their minimum energy requirements for maintenance, the low nutritional level was able to alter the metabolic and hormonal profile of this group of animals. The fasting period of 72 hours was characterized by a reduction in the concentration of glucose within the first 48 hours and recovery levels of this component in the maximum time of fasting, between 48 and 72 hours. This clearly associated with mobilization of lipid and protein reserves during fasting, which varied between groups, being higher in group free gain. The response of animals to fasting demonstrates the efficiency of mechanisms for maintaining energy homeostasis in these ensuring adequate physiological condition. The feedback period promoted significant recovery of energy status in the very first 24 hours. The effects of mobilization of body reserves were transient in animals, causing no damage or dysfunction in hepatic metabolism. The respirometry is a technique for accurately evaluating the nutritional requirements in cattle, since the methods imposed with regard to the physiological conditions of the animal during the evaluation.